Evaluation of antibiotic resistance patterns of Klebsiella isolates: Five-year observation (Annals of Medical Research, 2021)
Aim: Klebsiella spp. is a gram-negative rod, having many virulence factors such as capsule polysaccharides, adhesins, and determinants for iron acquisition. In this study, we aimed to determine the sub-species of Klebsiella spp. and their antibiotic resistance profiles isolated from a tertiary hospital in a five-year period.Material and Methods: The antibiotic resistance profiles of Klebsiella spp. isolated from various clinical specimens of patients between January 2014 and December 2018 were retrospectively reviewed.Results: In a total of 4506 isolates were investigated. Among those isolates, 2,254 were obtained from females and 2.252 were obtained from males. The mean age of the patients was 47.71±29.56 while the median age was 56 years. On the other hand, 2.150 (47.7%) of the isolates were obtained from hospitalized patients, while 2356 (52.3%) were obtained from outpatients. Among those isolates, 1.859 (41.3%) were ESBL positive and along with ESBL positive isolates, 802 were obtained from females and 1,057 were obtained from males and ESBL positivity was significantly more common in males (p:0.001). Moreover, ESBL positivity was significantly more common in patients older than 18 years of age compared with the patients younger than 18 years of age. Ciprofloxacin resistance was reaching 67.4% and Ertapenem resistance was as high as 39.1% in ESBL positive Klebsiella spp. Conclusion: In conclusion, ESBL positive and carbapenem resistant Klebsiella spp. strains are increasing. Multidrug resistant Klebsiella spp. strains may cause severe infections increasing mortality. In that aspect, the antibiotic resistance profile should be identified clearly and further studies regarding the preventive measures should be planned.
Keywords: Klebsiella; ESBL; antibiotic resistance; carbapenem.